Subclinical thyroid dysfunction and incident atrial fibrillation - a systematic review and meta-analysis. (24th May 2021) - Singh, H; Shahid, MZ; Harrison, SL; Lane, DA; Lip, GYH; Logantha, SJRJ
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): This project was supported by the MRes programme in the Institute of Life Course and Medical Sciences at The University of Liverpool. Thyroid hormones can act directly and indirectly on the cardiovascular system and studies have demonstrated associations between overt and subclinical thyroid dysfunction and adverse cardiovascular outcomes including heart failure, myocardial infarction, and coronary heart disease. The aim of this study was to assess the association between subclinical thyroid dysfunction and atrial fibrillation (AF). The protocol was registered on PROSPERO (CRD42020221565). MEDLINE and Scopus were searched from inception to 13th November 2020 for studies investigating subclinical thyroid dysfunction and incident AF. Risk of bias was assessed using the Risk of Bias Assessment Tool (RoBANS). The quality of evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) tool. Subgroup analysis was performed for post-operative and non-post-operative AF. 5413 records were identified. Nine cohort studies were suitable for inclusion in the systematic review, of which seven studies were included in the meta-analysis. The meta-analysis comprised 595, 058 patients. Subclinical hyperthyroidism was associated with a 99% increase in the risk of incident AF (Risk ratio (RR): 1.99; 95% confidence intervals (CI); 1.43 to 2.77; p < 0.0001; I² = 67%). Subclinical hypothyroidism was also associated with a greater risk of AF (RR: 1.24; 95% CI; 1.05 to 1.47; p = 0.01; I² = 65%). Subgroup analysis demonstrated a 76% increase in the risk of post-operative AF in patients with subclinical hypothyroidism compared to euthyroid post-operative patients (RR: 1.76; 95% CI; 1.36 to 2.28; p < 0.0001; I² = 0%). Six studies were rated as low risk of bias and three as medium risk of bias according to the RoBANS tool. The quality of evidence for AF in subclinical hyper- and hypothyroid patients was low. Subclinical hyperthyroidism and subclinical hypothyroidism were associated with a higher risk of incident AF and post-operative AF, respectively. The quality of the current evidence is low and ideally a randomised controlled trial should be conducted to confirm these associations and assess impacts of treatments.